Analisa Produktivitas Pemancangan Tiang Menggunakan Alat Pancang Diesel Hammer Pada Proyek Pembangunan Gedung Kantor Pengadilan Agama Dataran Hunipopu - Marasabessy, Ramona Istiqamah; Titaley, Henriette Dorothy; Abdi, Maslan n (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
Pile driving is an essential stage in foundation construction that helps ensure the stability and strength of the building structure. Piling can be done with various tools, including a diesel hammer. Diesel Hammer is known for its ability to deliver high-impact energy to the pile, enabling it to penetrate the soil effectively and efficiently. The purpose of this research is to determine the cycle time of the piling process and to determine the productivity of piling using diesel hammer tools. The method used in this research is direct observation to the field. The results obtained from the study are the average cycle time in the piling process using a diesel hammer piling tool at 101 points for 16 days, is 50.35 minutes during regular working hours and 59.94 minutes during overtime. The productivity of the diesel hammer on the work of the Religious Court Office Building was the lowest on the first day, at 10.48 m/hour, and the highest on day fifteen, at 17.25 m/hour. While in working overtime, the highest productivity occurred on the fifteenth day, at 16.71 m/hour, and the lowest on the first day, at 4.01 m/hour.Keywords: Produktivity, Pilling, Diesel Hammer